Partisipasi Masyarakat: Mendukung Keberhasilan Pengelolaan Hutan Rakyat - Andi Kurniawan; J.W. Hidayat; Amirudin Amirudin (xxxx-xxxx, 2020)
Kurniawan A, Hidayat JW, Amirudin A. 2020. PSociety participation: supporting the success of community forest management. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx.Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The development of community forestry policies in Indonesia has started since the old order era when the greening movement and the Karang Kitri movement were launched in 1956. The target of this movement is to plant yards and lands belonging to the community in the form of empty lands with useful plants, the results are quite sufficiently satisfying, especially in Java Island (Gunungkidul) and parts of Madura Island which were previously barren to become green areas. The success of community forest development and management cannot be separated from community participation, both direct and indirect participation. Community participation is their participation in an activity. In general, in community forest management, there are several activities including planning, planting, maintenance, harvesting, marketing, monitoring evaluation, and institutions. The extent of community involvement and participation in every stage of community forest management will be discussed in this article. It is hoped that high community participation will be in line with the level of success of community forest management so that a sustainable community forest will be realized. Besides, it is hoped that it will have a good impact on the economy, ecology, and social for the community.